Effectiveness and implementation of lower-intensity weight management interventions delivered by the non-specialist workforce in postnatal women: a mixed-methods systematic review - Fong, Mackenzie; Kenny, Ryan Patrick William; Thomson, Katie; Jesurasa, Amrita; Lavans, Amber; Patterson, Maddey; Sermin-Reed, Letitia; Nguyen, Giang; Aquino, Maria Raisa Jessica; Cullen, Emer; O'Keefe, Hannah; Moffat, Malcolm; et al. (Frontiers in Public Health, 2024)
Lower-intensity interventions delivered in primary and community care contacts could provide more equitable and scalable weight management support for postnatal women. This mixed-methods systematic review aimed to explore the effectiveness, implementation, and experiences of lower-intensity weight management support delivered by the non-specialist workforce. We included quantitative and qualitative studies of any design that evaluated a lower-intensity weight management intervention delivered by non-specialist workforce in women up to 5 years post-natal, and where intervention effectiveness (weight-related and/or behavioural outcomes), implementation and/or acceptability were reported. PRISMA guidelines were followed, and the review was prospectively registered on PROSPERO (CRD42022371828). Nine electronic databases were searched to identify literature published between database inception to January 2023. This was supplemented with grey literature searches and citation chaining for all included studies and related reviews (completed June 2023). Screening, data extraction and risk of bias assessments were performed in duplicate. Risk of bias was assessed using the Joanna Briggs Institute appraisal tools. Narrative methods were used to synthesise outcomes. Seven unique studies described in 11 reports were included from the Netherlands (n = 2), and the United Kingdom, Germany, Taiwan, Finland, and the United States (n = 1 each). All studies reported weight-related outcomes; four reported diet; four reported physical activity; four reported intervention implementation and process outcomes; and two reported intervention acceptability and experiences. The longest follow-up was 13-months postnatal. Interventions had mixed effects on weight-related outcomes: three studies reported greater weight reduction and/or lower postnatal weight retention in the intervention group, whereas four found no difference or mixed effects. Most studies reporting physical activity or diet outcomes showed no intervention effect, or mixed effects. Interventions were generally perceived as acceptable by women and care providers, although providers had concerns about translation into routine practice. The main limitations of the review were the limited volume of evidence available, and significant heterogeneity in interventions and outcome reporting which limited meaningful comparisons across studies. There is a need for more intervention studies, including process evaluations, with longer follow-up in the postnatal period to understand the role of primary and community care in supporting women’s weight management. Public Health Wales was the primary funder of this review.